THE INFLUENCE OF COLLABORATIVE WRITING TOWARDS STUDENTS’ DESCRIPTIVE WRITING ABILITY - Destia Herlisya, Destia (LPPM STKIP PGRI Bandar Lampung, 2019)
The research reports on the Influence of Collaborative Writing Towards Student’s Descriptive Writing Ability. Collaborative writing technique was applied in this research to improve the student’s descriptive writing ability. The aims of the research were to know and to describe student’s descriptive writing ability and to know and to describe whether there is influence of Collaborative writing towards students’ descriptive writing ability. The research was conducted by using a quasi-experimental design with pre test and post test. The population of this research are the students at the first semester of the tenth class at SMA Adiguna Bandar Lampung that consisted of 49 students in 2 classes. The sample of this research were two classes, they were as control class and experimental class. Control class was taught by Individual writing while experimental class was taught by Collaborative writing. In getting the data, the writer used writing test. The result showed that based on the calculation, the writer got that = 5.54 and = 1.68 and 2.42. It means that . So, Ho is rejected and Ha is accepted. From the result above, the writer states that there is significance influence of collaborative writing towards students’ descriptive writing ability of the tenth class of the first semester at SMA Adiguna Bandar Lampung.